Adversity Quotient on Moslem Teens Drug Addicts - Putra, Laksamana Pagar Alam Dimas; Budiman, Budiman; Reza, Iredho Fani (Indonesian Journal of Behavioral Studies, 2021)
Drug abuse in Indonesia has become increasingly troubling. The spread of drugs is now widely spread in society, especially in adolescents. Drug stands for narcotics, psychotropic and other active ingredients. In a broad sense, drugs are drugs, materials or substances. When this substance enters the human body, either orally (by mouth), or inhaled or through an injection, it will affect the work of the brain or the central nervous system and disturb the physical and psychological. This study uses phenomenological qualitative research methods because a truth can be obtained by capturing phenomena or symptoms that radiate from the object of research. The subjects of this study were three teenage boys who became drug addicts. The data collection method in this study used semi-structured interviews and indirect observation. There are three stages of data analysis techniques: data reduction, data display, concluding drawing/verification. Meanwhile, to test the validity of the data, researchers used Credibility (internal validity), Dependability test (reliability), and Confirmability test (objectivity) of the data. The results of the study found that the subject's adversity quotient had an important role in breaking away from drugs. The three subjects were able to make the problems they faced as a motivation to rise from adversity. Meanwhile, to test the validity of the data, researchers used Credibility (internal validity), Dependability test (reliability), and Confirmability test (objectivity) of the data. The results of the study found that the subject's adversity quotient had an important role in breaking away from drugs. The three subjects were able to make the problems they faced as a motivation to rise from adversity. Meanwhile, to test the validity of the data, researchers used Credibility (internal validity), Dependability test (reliability), and Confirmability test (objectivity) of the data. The results of the study found that the subject's adversity quotient had an important role in breaking away from drugs. The three subjects were able to make the problems they faced as a motivation to rise from adversity.